Investigation into irradiation effects in ODS steels using ion implantation and micromechanical testing - Grieveson, E; Roberts, S; Grieveson, E; Roberts, S (IEEE, 2013)
Oxide Dispersion Strengthened steels are materials for the first wall of proposed nuclear fusion reactors including DEMO. They contain a nanoparticle dispersion of Y2O3 which restricts dislocation motion. The particles act as low energy sites capable of trapping helium. The experiments reported here focus on the mechanical effects of ion implantation on a model Fe-Cr alloy and an ODS equivalent. Samples were helium and iron ion implanted as a simulation of neutron damage and material transmutation. The main restriction of using ion implantation is the limited damage depth available in samples (<3μm), therefore nanoindentation was used to provide information on the surface hardness changes. Transmission Electron Microscopy was used to see how the dislocation structure within these test volumes changes with implantation.